Unsteady free surface flow in a storm drain: general and analytical study - Yevjevich, Vujica M., 1913-, author; Colorado State University, publisher (Colorado State University. Libraries, 1961)
This report represents an analytical investigation of unsteady free surface flow in a storm drain. As a preliminary general study its broad scope is the outline of problems, the selection of mathematical tools and procedures, and the elaboration of a general approach for further studies by hydraulic model and by digital computer investigations in order to develop a set of routing methods for storm drain floods. Each method of this set should be feasible to the particular conditions of data available of flood hydrographs and storm drain characteristics, as well as of precision of computation. The initial and boundary conditions, applications, and the general approach selected are briefly enumerated in the introduction. The two partial differential equations for unsteady flow are derived and discussed. These basic mathematical tools serve as the starting equations for the computation of all high-order approximations of unsteady flow. Characteristic curves are derived and discussed. The integration of differential equations by method of finite differences is treated in detail, with special attention given to boundary problems. The coefficients of differential equations are analyzed. Particular attention is given to geometric characteristics of conduit drains, to velocity distribution coefficients, to flow resistance and to lateral flows, in order to treat their functions which are introduced in the two partial differential equations. The initial and boundary data are analyzed: for flow before the storm flood enters the drain; for inflow hydrographs; for data of junction problems when main drains meet; for outflow conditions; and for data of general boundary conditions. The end of the report contains the specific aims of the future research program, methods and procedures to be used (especially hydraulic studies, digital computer studies and comparative studies for the results of these two procedures), significance and characteristics of the future research and finally the facilities either available now, or to be installed in the near future in order to enable the research program to be carried out.
CER61VMY38.
June 1961.
Keywords: Groundwater; Seepage; Groundwater flow